The widow of Wall Street : a novel - Meyers, Randy Susan (Atria Books, 2017)
Putting her complete trust in her husband as he builds a financial empire, Phoebe is shattered when she discovers that her husband's successes are tied to an elaborate Ponzi scheme, a situation that forces her to make a terrible choice.